The effect of differentiated learning approach based on learning style on critical thinking skills and mathematical problem solving of junior high school students PAB 5 Patumbak - Yunanda, Erni; Salayan, Madyunus; Zahari, Cut Latifah (Institute of Computer Science (IOCS), 2025)
The objectives of this study are 1) to analyze the influence of differentiated learning approaches based on learning styles on students' critical thinking skills and mathematical problem solving, 2) to analyze significant differences in critical thinking skills between students with different learning styles (e.g. visual, auditory, kinesthetic) after following the differentiated learning approach and 3) to analyze the influence of differentiated learning approaches tailored to students' learning styles on students' mathematical problem-solving abilities. The form of research used by the researcher is One-group Pretest-Posttest Design. The sample in this study is all students of grades VII-1, VII-2 and VII-3. Based on the results that have been carried out, it is obtained that 1) there is a significant influence between differentiation learning based on learning styles on the critical thinking ability and mathematical problem solving of students, 2) there is a significant difference in critical thinking skills between students with different learning styles after participating in differentiated learning and 3) there is a significant influence between differentiation learning that is adjusted to the learning style of students to the mathematical problem-solving ability of students.